Fa’ālīyatu Istikhdāmi Wasāili al-Qiṣṣoh al-Ṣūriyyah Litarqiyati Mahārati al-Kitābah bi al-Lughati al-‘Arabiyyah: (Dirāsah Tajrībiyyah Nahwa Thullābi al-Faṣli al-Sābi’ Fī al-Madrasati al-Tsānawiyah al-Tarbawiyah Tamberu Sampāng Madūra) - Moh. Sulton (Lughawiyyat: Jurnal Pendidikan Bahasa dan Sastra Arab, 2020)
ABSTRACT This research was conducted owing to numerous students who felt bored as they followed Arabic learning which it was triggered by the method of teaching used by the teacher relying on the lecture method only. Moreover, there was an enormous number of students feeling hard associated with applying what they have acquired in the class, for instance arranging simple sentences and so on. Meanwhile, the purpose of this research was to know whether there was an impact of comic medium usage in improving writing capability in terms of Arabic learning of students whose grade was 7th at Islamic Junior High School At-Tarbawiyah East Tamberu Sampang Madura as well as to find out how big the effect of the comic medium itself. This research was a quantitative one using an experimental study whose data was obtained from the students of 7th grade of Islamic Junior High School At-Tarbawiyah East Tamberu Sampang Madura with the figure of 30 teenagers. Furthermore, the researcher divided that amount into two groups. While the first group called The Controlling Group encompassed 15 students, the second group named The Experimental Group consisting of the same amount, 15 students. The data collection techniques used in this research were Pre-Test and Post-Test whereas the data analysis technique used the T-Test, with the analysis data requirement which should distribute Normality and Homogeneity. From the result of the data analysis, it testified that the score of the experimental group (37.3) was considerably higher in comparison with that of the controlling class (20.0), and it illustrated that there was a remarked impact of comic media usage in accordance with developing the writing competency of Arabic learning toward the students of 7th grade at Islamic Junior High School At-Tarbawiyah East Tamberu Sampang Madura with the substantially high discrepancy of range, at 17.3. Keywords : Comic Medium, Writing Proficiency.